Parkin Suppresses c-Jun N-terminal kinase-induced cell death via transriptional regulation in Drosophila. - Hwang, S.; Kim, D.; Choi, G.; An, S.W.; Hong, Y.K.; Suh, Y.S.; Lee, M.J.; Cho, K.S. (Molecules and Cells, 2010)
Parkin is the most prevalent genetic factor in the onset of autosomal recessive juvenile parkinsonism (AR-JP), and mutations in parkin has been reported to cause motor defects, which result from dopamine deficiency caused by dopaminergic neuronal cell death. Activation of c-Jun N-terminal kinase (JNK) has also been implicated in neuronal cell death in Parkinson's disease (PD). Moreover, Drosophila models for AR-JP, loss of function mutants of Drosophila parkin, also show dopaminergic neural degeneration associated with hyperactivation of JNK, increased apoptosis, and mitochondrial defects. However, the molecular mechanism by which Parkin protects cells from apoptosis remains unclear. In the present study, we tested whether Drosophila Parkin suppressed the JNK signaling pathway in developing tissues. Ectopically expressed parkin strongly suppressed the constitutively active form of Hemipterous (Hep(CA)), a Drosophila JNK kinase that induces an eye degeneration phenotype and apoptosis in the eye imaginal disc. Moreover, parkin also suppressed extra vein formation induced by Basket (Bsk), a Drosophila JNK. Interestingly, the bsk mRNA level was markedly reduced by parkin over-expression, suggesting that the effect of parkin on the phenotype induced by activation of JNK signaling was achieved by transcriptional regulation. Furthermore, we found that the expression level of JNK target genes was reduced by parkin over-expression. Taken together, these results suggest that Drosophila Parkin suppresses JNK signaling by reducing bsk transcription.